2013
DOI: 10.5539/ass.v9n15p305
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Governance Structure and Its Relationship with Audit Fee-Evidence from Malaysian Public Listed Companies

Abstract: This study investigates the relationship between the firms' internal corporate governance mechanisms with audit fee in Malaysia. Different to other study conducted previously, this study also looks at the objectives of the study from the perspective of the newly introduced Malaysian Code of Corporate Governance (MCCG 2007)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…In private sector such as for the public listed company, accountability and good governance mechanism are importance to protect the right of the shareholders and other stakeholders (Hamid et al, 2011). This can be done via reliable financial reporting (Asmuni et al, 2015;Saudagaran and Diga, 1997), higher quality of the statutory audit (Husnin et al, 2016;Knechel et al, 2013;Goodwin-Stewart and Kent, 2006), audit committee monitoring (Pandit et al, 2017;Husnin et al, 2013;Klein, 2002), voluntary non-financial information disclosure (Schoenfeld, 2017;Jaafar et al, 2014;Hashim et al, 2014;Eng and Mak, 2003), linked pay-forperformance of directors' remuneration (Madlela and Cassim, 2017;Ahmad et al, 2016;Gregg et al, 1993) and good control system (Chen et al, 2017;Suhaimi et al, 2016;Doyle et al, 2007). However, managing public fund in public sector is not easy because it involves tax payers' money, and hence, requires heavier accountability.…”
Section: Literature Review 21 Accountability From Public Sector Persp...mentioning
confidence: 99%
“…In private sector such as for the public listed company, accountability and good governance mechanism are importance to protect the right of the shareholders and other stakeholders (Hamid et al, 2011). This can be done via reliable financial reporting (Asmuni et al, 2015;Saudagaran and Diga, 1997), higher quality of the statutory audit (Husnin et al, 2016;Knechel et al, 2013;Goodwin-Stewart and Kent, 2006), audit committee monitoring (Pandit et al, 2017;Husnin et al, 2013;Klein, 2002), voluntary non-financial information disclosure (Schoenfeld, 2017;Jaafar et al, 2014;Hashim et al, 2014;Eng and Mak, 2003), linked pay-forperformance of directors' remuneration (Madlela and Cassim, 2017;Ahmad et al, 2016;Gregg et al, 1993) and good control system (Chen et al, 2017;Suhaimi et al, 2016;Doyle et al, 2007). However, managing public fund in public sector is not easy because it involves tax payers' money, and hence, requires heavier accountability.…”
Section: Literature Review 21 Accountability From Public Sector Persp...mentioning
confidence: 99%
“…Likewise, Farooq et al (2018) examined five years data of KSE-100 and found effective board quality has positive association but audit committee effectiveness reduces the external audit fee. Husnin et al (2013) scrutinized internal corporate governance mechanisms with audit fee in Malaysia and found that the Malaysian Code of Corporate Governance influenced the determinants of audit fee. Hamza (2018) studied 26 Jordanian insurance companies and found significant impact of corporate governance principles on the auditor's independence and audit fees.…”
Section: Introductionmentioning
confidence: 99%